Are overeating and food addiction related to distress tolerance? An examination of residents with obesity from a U.S. metropolitan area. Issue 3 (May 2017) - Kozak, Andrea T.; Davis, Jessica; Brown, Ryan; Grabowski, Matthew
Summary: Objective: Low distress tolerance (DT) is an inability to handle negative emotions. There is strong support for the connection between low DT and substance addiction, which suggests that the former might be related to food addiction (FA). Previous work found that low DT was related to overeating in a college sample. The current study had two primary aims: (1) to determine whether low DT is associated with overeating in a sample of participants with diverse races and incomes, and (2) to investigate the relationships among DT and body mass index (BMI) as well as DT and FA symptoms. DT as a moderator of the association between general overeating and FA was also explored. Methods: One hundred and ninety residents of Metropolitan Detroit communities (mean age: 41.71; 45.8% male; 34.7% non-White race; 47.4% with obesity) completed the DT Scale, Dutch Eating Behavior Questionnaire, Three Factor Eating Questionnaire, and Yale FA Scale. BMI was based on measured weight and height. Results: After adjusting for covariates, linear regression models found significant negative relationships between DT and emotional eating ( P < 0.001), external eating ( P < 0.001), disinhibition ( P < 0.001), FA ( P < 0.001), and BMI ( P < 0.01). DT was determined to be a moderator, such that among individuals who endorsed high levels of overeating, those with low DT reported more FA symptoms than those with high DT. Conclusion: These findings suggest interventions targeting low DT should be considered to reduce overeating, which is a precursor and maintenance factor of obesity and FA.